(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
The present was undertaken with the objective of evaluating the status of autopsy teaching in India, reasons for decline/death of autopsy teaching, and to evaluate perception of the forensic medicine faculties about autopsy teaching. A Google form-based survey was conducted among the Forensic Medicine faculties across India. About 115 participants across India working in Government or private institutes as professors to tutors/demonstrators took part in this study. About 71.3% participants were involved in conducting medico-legal autopsies. Majority of the participants agreed that observation of medico legal autopsy helps the students in learning anatomy, traumatic wounds, core areas of Forensic Medicine and Toxicology, pathology of disease and clinical reasoning skills. About 66.1% participants agree that students are comfortable to view medicolegal autopsies by standing next to dissecting table. About 80.9% participants agree that lack of permission from State Government to start the medico-legal autopsies at the private medical institutes is the reason for decreased autopsy teaching. Other factors for decline in autopsy teaching include lack of motivation from forensic faculties to conduct autopsies, limited curriculum time, increased departmental works with limited staff, and insufficient autopsies at their centre. About 86.9% participants agree that National Medical Commission guidelines ‘not mandatory to have autopsy facilities in medical college’ is a setback for the learning from autopsy. We conclude that autopsy teaching is beneficial in learning anatomy and understanding pathology of disease. A better facility such as clean autopsy environment, glass partition with projection of autopsy procedure and good faculty interaction with students would help in increasing the autopsy teaching.